PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT UNTUK MENINGKATKAN KONSEP PEMAHAMAN SISTEM TATA SURYA - Isti qoma; Violita Atika Putri; Mochammad Rafly Ad'ha; Arie Widya Murni (ELENOR: Elementary School Journal, 2024)
The development of ICT-based learning media is used by teachers in delivering material to students to facilitate understanding and critical thinking. This research uses the ADDIE method for data collection techniques using the results of interviews and questionnaires. The ICT-based learning media developed by this researcher was declared suitable for use as teaching material in the form of media and materials that are simple and easy to understand. The percentage obtained by researchers from the interview results was 90% or the criteria were declared suitable for application in science learning in elementary schools.